Robotic teleoperation systems using a wearable multimodal fusion device. (6th July 2017) - Fang, Bin; Sun, Fuchun; Liu, Huaping; Guo, Di; Chen, Wendan; Yao, Guodong
Teleoperation is of great importance in the area of robotics especially when people's presence at the robot working space is unavailable. It provides an alternative to employ human intelligence in the control of the robot remotely. We establish robotic teleoperation systems with a wearable multimodal fusion device. The device is integrated with 18 low-cost inertial and magnetic measurement units, which cover all segments of the arm and hand. The multimodal fusion algorithm based on extended Kalman filter is deduced to determine the orientations and positions of each segment. Then, the robotic teleoperation systems using the proposed device are designed. The novel teleoperation schemes can be applied for 11DOF robotic arm–hand system and 10DOF robotic arm–hand system, in which the operator's fingers are used for robotic hand teleoperation, and the arms with palm are used for robotic arm teleoperation. Meanwhile, the proposed robotic teleoperation systems are fully realized with a user-friendly human–machine interaction interface. Finally, a series of experiments are conducted with our robotic teleoperation system successfully.